Konstruksi Makna Pegawai terhadap MONSAKTI dalam Transparansi dan Akuntabilitas Keuangan Publik - Febbbyana Andra Vesco; Fachruzzaman Fachruzzaman (Forum Kerjasama Pendidikan Tinggi, 2026)
Digital transformation in public financial governance demands increased transparency and accountability through the use of online-based information systems. One implementation is the use of the MONSAKTI application at the Bengkulu Province National Land Agency (BPN) Regional Office as a financial management monitoring instrument. This study aims to analyze employee interpretations of MONSAKTI's role in supporting transparency and accountability in public financial management. The study uses an interpretive qualitative approach with a phenomenological perspective to understand the experiences, perceptions, and construction of meaning for employees as system users. Eight informants from the Finance and BMN Subdivisions were selected purposively based on their direct involvement in the use of MONSAKTI. MONSAKTI. Data collection was conducted through in-depth interviews, observation, and documentation studies, then analyzed in stages through the process of organizing data, reducing information, presenting findings, identifying patterns, and drawing conclusions using triangulation techniques to maintain data credibility. The results of the study indicate that employees' meaning of MONSAKTI is formed in layers through four main patterns, namely instrumental legitimacy through ease of monitoring and administrative efficiency, reconfiguration of accountability through digital supervision and work activity track records, structured transparency based on the hierarchy of organizational authority, and differentiation of meaning based on employee position and work experience. The research findings indicate that the success of public financial digitalization is not only determined by the quality of technology, but also by the ability of users to build an understanding of the system's functions in everyday bureaucratic practices. This research contributes to the development of understanding of public sector financial digitalization from a user-defined perspective, by demonstrating that employees' understanding of MONSAKTI is formed in layers through work experience, digital oversight functions, structured transparency, and differences in organizational positions. These findings expand studies of public sector digital transformation, which have previously focused more on the effectiveness of administrative systems.